Diversity and Social Capital in the U.S: A Tale of Conflict, Contact or Total Mistrust? - Willie Belton; Yameen Huq; Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2014)
In this paper we explore the relationship between ethnic fractionalization and social capital. First, we test for time differences in the impact of ethnic fractionalization on social capital using U.S. data from 1990, 1997 and 2005. Subsequently we examine the data for evidence of the conflict, contact and hunker-down theories espoused by Putman in explaining what happens over time when individuals interact with those of differing ethnicities. We find no evidence of heterogeneity in the impact of ethnic fractionalization on social capital over time. In addition we find evidence of the conflict theory and no evidence of hunker-down or contact theories. Our results suggest that as communities become more diverse, there is a tendency for social capital to decline.
Keywords: D71; Z10; J10; J19; 330; ethnic fractionalization; social capital; trust; diversity; social networks